Guidelines in human resources management - Neves, Carmo (2016)
The purpose of this communication is to address the management of human resources in the organizations. The aim is to discuss a range of issues that are likely to be applied in the management of human resources, such as management skills, organizational development, and administrational management (also known as payroll issues). Reference is also made to some support tools for decision making as well as the coaching process in the management of human resources. The methodology used is based on a personal reflection of two decades of professional experience in the management of organizations and human resources and on the bibliographic review on this subject. We highlight the following main conclusions: (1) the integration of management of human resources in the organizational strategy optimizes the entire process of organizational development, contributing to excellence. In this sense we emphasize the importance of the management of human resources being closely in collaboration and attuned to the administration, fact which will optimize the entire process, (2) the management of human resources implies the managing of people as a resource (in its more technical and economistic way) without running out of it and it is also essential to see people as individuals (humans) with their values, beliefs, identities, attitudes and behaviours, (3) despite these evidences most organizations continue to focus their practice on the operationalization of people as a mere resource, being